25.0k views
2 votes
Solve for x: 2x+1= -3x+36

User Zain Patel
by
4.6k points

2 Answers

7 votes

Answer:

first you would add 3x to -3x and 2x, then you would get 5x+1=36. Then you subtract 1 from 1 and 36. Then you get 5x=35. Then you divide by 5 to get the answer 7. so your answer is x=7

Explanation:

hope this helps

User Hemant Rao
by
4.7k points
7 votes

Answer:

x = 7

Explanation:

2x + 1 = -3x + 36

2x + 3x + 1 = -3x + 3x +36

5x + 1 = 36

5x + 1 - 1 = 36 - 1

5x = 35

5x/5 = 35/5

x = 7

User Iamiddy
by
5.6k points